Identification of inferior pancreaticoduodenal artery during pancreaticoduodenectomy using augmented reality‐based navigation system. Issue 4 (22nd August 2013) - Onda, Shinji; Okamoto, Tomoyoshi; Kanehira, Masaru; Suzuki, Fumitake; Ito, Ryusuke; Fujioka, Shuichi; Suzuki, Naoki; Hattori, Asaki; Yanaga, Katsuhiko
Abstract Background In pancreaticoduodenectomy (PD), early ligation of the inferior pancreaticoduodenal artery (IPDA) before efferent veins has been advocated to decrease blood loss by congestion of the pancreatic head to be resected. In this study, we herein report the utility of early identification of the IPDA using an augmented reality (AR)‐based navigation system (NS). Methods Seven nonconsecutive patients underwent PD using AR‐based NS. After paired‐point matching registration, the reconstructed image obtained by preoperative computed tomography (CT) was fused with a real‐time operative field image and displayed on 3D monitors. The vascular reconstructed images, including the superior mesenteric artery, jejunal artery, and IPDA were visualized to facilitate image‐guided surgical procedures. We compared operating time and intraoperative blood loss of six patients who successfully underwent identification of IPDA using AR‐based NS (group A) with nine patients who underwent early ligation of IPDA without using AR (group B) and 18 patients who underwent a conventional PD (group C). Results The IPDA or the jejunal artery was rapidly identified and ligated in six patients. The mean operating time and intraoperative blood loss in group A was 415 min and 901 ml, respectively. There was no significant difference in operating time and intraoperative blood loss among the groups. Conclusions The AR‐based NS provided precise anatomical information, which allowed the surgeons to rapidly identify and perform early ligation of IPDA in PD.